Remedesivir-induced newly onset type 2 diabetes mellitus (Indian Journal of Case Reports, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by an elevation in blood glucose levels. During the COVID-19 pandemic, Remdesivir, an antiviral drug originally used to treat Hepatitis B, was later approved for use in COVID-19 treatment. It is important to be aware of rare but serious adverse events associated with Remdesivir therapy, particularly in patients without known comorbidities. In this report, we elaborate on a case of drug-induced Type-2 diabetes mellitus in a man who was healthy with no other comorbidities but was diagnosed with COVID-19. The patient’s blood glucose levels were significantly increased with Remdesivir therapy. On withholding the drug, the patient’s blood glucose levels dropped, and they elevated again once it was re-administered and continued. Therefore, it is crucial to routinely monitor the blood glucose levels in patients receiving Remdesivir therapy to avoid such adverse effects.